Personality Traits and Non-Suicidal Self-Injury among Young Adolescents - Kayla Camille M. Agos; Daniela Tricia D. Batino; Portia R. Marasigan (International Review of Social Sciences Research, 2021)
The study determined the personality traits and the level of non-suicidal injury (NSSI) among the young adolescents of Tiaong, Quezon in the Philippines. A descriptive-correlational research design was used with 70 participants selected through purposive sampling technique. The participants were mostly 18 years old, women, first born children and Roman Catholic. The questionnaire was divided into three parts: respondents’ profile as to age, gender, religion, and birth order; the NSSI to assess the self-harm inventory and Big Five Inventory to describe the respondents’ personality. Results revealed the respondents’ personality with high level of openness to new experience but with severe level of NSSI. It was further revealed that only religion has a significant relationship to NSSI. The results imply that adolescents open to new experience have tendencies to commit non-suicidal self-injury.